If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -5j + 1 = -3j + 9 Reorder the terms: -6 + 1 + -5j = -3j + 9 Combine like terms: -6 + 1 = -5 -5 + -5j = -3j + 9 Reorder the terms: -5 + -5j = 9 + -3j Solving -5 + -5j = 9 + -3j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '3j' to each side of the equation. -5 + -5j + 3j = 9 + -3j + 3j Combine like terms: -5j + 3j = -2j -5 + -2j = 9 + -3j + 3j Combine like terms: -3j + 3j = 0 -5 + -2j = 9 + 0 -5 + -2j = 9 Add '5' to each side of the equation. -5 + 5 + -2j = 9 + 5 Combine like terms: -5 + 5 = 0 0 + -2j = 9 + 5 -2j = 9 + 5 Combine like terms: 9 + 5 = 14 -2j = 14 Divide each side by '-2'. j = -7 Simplifying j = -7
| 12x-6=3(x+9) | | 13(x-2)=8x-6 | | 123456790*23456789+1234567890= | | 10=-30x+10 | | (w)=0 | | .25(12+x)=.6+.35x | | 9p^2-12p=0 | | (w)=1 | | (w)=-1 | | -9n^2-9=315 | | 5+6x+25=180 | | (w)=-2 | | 8-10p=88 | | 4c-10=-9+3c | | (7y+2)(y-5)= | | 8x(8+6x)=20 | | .25(12x)=.6+.35x | | -2(x-4)=-6(2+x) | | 5(x+1)+51=-2x | | 4x+14=6x-26 | | 2m+7(m-1)=-21-5m | | 5+6y=5y+10 | | -abx^2+bcx+1=0 | | 5+y^2+7=3 | | 15w-22=-111 | | 8v+4=2v-8 | | 4(x-4)+2x=4x-6 | | (6y+5)(y-2)= | | 13x+7=6x+14 | | -3+7q=-7+9q | | -(1+6m)+6m=-11+3(r-7) | | Y=(5t^2)*(5t^3) |